Was the Anthropocene anticipated?. (April 2015) - Hamilton, Clive; Grinevald, Jacques
Various authors have identified 'precursors' of the new concept of the Anthropocene, with most frequent reference made to Antonio Stoppani, Vladimir Vernadsky and Pierre Teilhard de Chardin. The effect, intended or otherwise, of finding forerunners is to deflate the significance of the proposed new geological epoch. We argue there were no precursors to the notion of the Anthropocene, and that there could not have been because the concept (put forward in the year 2000) is an outgrowth of the recent interdisciplinary understanding of the Earth as an evolving planet inaugurated in the 1980s by the International Geosphere-Biosphere Programme and Earth system science. Earlier scientists who commented on 'the age of man' did so in terms of human impact on the environment or 'the face of the Earth', not the Earth system . Moreover, earlier Western conceptions relied on a progressive and linear evolutionary understanding of the spread of humankind's geographical and ecological influence, whereas the Anthropocene represents a radical rupture with all evolutionary ideas in human and Earth history, including the breakdown of any idea of advance to a higher stage (such as Teilhard's 'noösphere').